Matrix liposomes: a solid liposomal formulation for oral administration - Pantze, Silvia; Parmentier, Johannes; Hofhaus, Götz; Fricker, Gert (European journal of lipid science and technology, 2014)
Liposomes can be used as oral dosage form to improve the bioavailability of both hydrophilic drugs, such as peptides and proteins and lipophilic drugs. But liposome dispersions are not very stable under the harsh conditions of the GI-tract. Also a controlled release of embedded compounds is not possible. Therefore we developed a lipid based liposomal carrier system for peroral delivery of peptides. The lipid bilayer of standard egg-PC/cholesterol liposomes were stabilized by gelatine. The gelatine also works as a thickening agent by forming a matrix in which liposomes are embedded. Liposomes were prepared by dual asymmetric centrifugation with the addition of gelatine. Size and size distribution of prepared liposomes with up to 20% gelatine achieved the same quality compared to conventional liposomes. Size and size distribution, encapsulation efficiency of different compounds and the dissolution behaviour of the solid dosage form in simulated intestinal fluid were examined. Matrix liposomes containing 20% gelatine showed an approximately linear release of liposomes. Moreover, the dissolution rate could be adjusted by modification of the gelatine concentration and the absolute amount of liposomes released at a certain time was found to be dose dependent. Practical applications: The new liposomal solid formulation can be useful for a controlled release of hydrophilic macromolecules as peptides and proteins after peroral administration. Liposomes embedded in a solid dosage form offer the possibility of a simple administration and exhibit higher storage stability compared to liposomes in dispersion. A composition of phospholidpids and gelatine leads to matrix liposomes prepared by dual asymmetric centrifugation. Dissolution of the solid liposomal formulation leads to a liposome release out of the dosage form. The dissolution rate can be adjusted by the concentration of gelatine.